Implementation of the Quasi-Brittle Damage Model for 2024 Aluminum Alloy under Periodic Loading - Sadegh Ghorbanhosseini; saeed yaghoubi (International Journal of Advanced Design and Manufacturing Technology, 2019)
Damage mechanics is one of the most important parts of mechanical engineering that determines the time life for different mechanical elements. The most various models that have been provided so far in damage mechanics, are related to ductile or brittle damage. Nowadays, the investigation of materials by ductile-brittle damage behavior has been considered by researchers. Kintzel quasi-brittle damage model is one of the best damage models in this field. Therefore, in this paper, due to the application of 2024 Al alloy in different industries especially aerospace and the ductile-brittle damage behavior of this alloy, the implementation of the Kintzel quasi-brittle damage model is presented. For this purpose, by writing an explicit user subroutine VUMAT in finite element software (ABAQUS), a test sample under periodic loading has been modeled. The results of this research showed that the complete failure occurs after the 12th cycle under a periodic loading. Also, 2024 Al alloy showed a good ultimate tensile strength (about 400 MPa) under periodic loading. The magnitude of ductile and brittle damage variables are 0.23 and 0.38, respectively.